OLIG2 is a novel immunohistochemical marker associated with the presence of PAX3/7-FOXO1 translocation in rhabdomyosarcomas - Magdalena Kaleta; Anna Wakulińska; Agnieszka Karkucińska-Więckowska; Bożenna Dembowska-Bagińska; Wiesława Grajkowska; Maciej Pronicki; Maria Łastowska (BMC, 2019)
Abstract Background The most frequent histological types of rhabdomyosarcoma (RMS) in children are embryonal (ERMS) and alveolar (ARMS) tumours. The majority of ARMS are characterized by the presence of PAX3/7-FOXO1 gene fusion and have a worse prognosis than fusion gene-negative ARMS. However, identification of PAX3/7-FOXO1 fusion status is challenging when using formalin-fixed, paraffin-embedded (FFPE) material. Microarray analyses revealed that high expression of several genes is associated with PAX3/7-FOXO1 fusion status. Therefore, we investigated if immunohistochemical approach may detect surrogate marker genes as indicators of fusion gene-positive RMS. Methods Forty five RMS patients were included in the analysis and immunohistochemistry was applied to FFPE tissues collected at diagnosis. Protein expression of OLIG2, a novel marker in RMS, was investigated using antibody EP112 (Cell Marque). In addition already known two markers were also analyzed: TFAP2B using rabbit anti-TFAP2β antibody (Santa Cruz Biotechnology) and ALK using anti-ALK antibody clone D5F3 #3633 (Cell Signalling). Fluorescence in situ hybridization (FISH) was performed on FFPE sections with FOXO1/PAX3 and/or FOXO1/PAX7 probes (Dual Colour Single Fusion Probe, Zytovision). Results Our analysis revealed that all three immunohistochemical markers are associated with the presence of PAX3/7-FOXO1 fusion: TFAP2B (p < 0.00001), OLIG2 (p = 0.0001) and ALK (p = 0.0007). Four ARMS had negative PAX3/7-FOXO1 status and none of them displayed positive reaction with the analysed markers. Positive reaction with OLIG2 (6 tumours) was always associated with the presence of PAX3/7-FOXO1 rearrangement. Two additional OLIG2 positive cases showed inconclusive FISH results, but were positive for TFAP2B and ALK, what suggests that these tumours expressed fusion positive signature. Conclusion Our results indicate that TFAP2B, ALK and a novel marker OLIG2 may serve as surrogate markers for PAX3/7-FOXO1 status what is especially beneficial in cases where poor quality tumour tissue is not suitable for reliable genetic analyses or shows inconclusive result.